Novel super nanocomposite (CeO-SiO2 nanocomposite) with enhanced biological application: Synthesis and characterization - G. Sabeena; S. Vainath praveen; E. Pushpalakshmi; S. Rajaduraipandian; G. Annadurai (Plant Nano Biology, 2023)
Cerium Oxide nanoparticles (CeO NPs), Silica nanoparticles (SiO2 NPs), and CeO-SiO2 nanocomposite (Super Nanocomposite) are some of the most promising new developments in the field of investigation. One of the most popular metal oxide nanocomposites in biological applications is CeO-SiO2 nanocomposite (Super Nanocomposite), which has excellent biocompatibility and is also inexpensive and low-toxic. CeO nanoparticles (CeO NPs), Silica nanoparticles (SiO2 NPs), and CeO-SiO2 nanocomposite (Super Nanocomposite) have all demonstrated promise in the field of biomedicine, particularly in the anti-diabetic, anti-inflammatory, and antibacterial fields. In order to combat various bacterial species, Super Nanocomposite concentrations (50 µL/mL) were developed. In this case, silica nanoparticles (SiO2 NPs), cerium oxide nanoparticles (CeO NPs), and CeO-SiO2 nanocomposite (Super Nanocomposite) have greater antibacterial activity in the zone of inhibition. SiO2 NPs, CeO NPs, and CeO-SiO2 Nanocomposite (Super Nanocomposite) various in-vitro biological activities were also assessed, including their anti-inflammatory and anti-diabetic properties. In comparison to SiO2 NPs and CeO NPs, Super Nanocomposite exhibits greater anti-inflammatory and anti-diabetic characteristics. In this study, SiO2 NPs, CeO NPs, and CeO-SiO2 nanocomposite (Super Nanocomposite) were produced using a basic precipitation method. It was established that SiO2 NPs, CeO NPs, and CeO-SiO2 Nanocomposite (Super Nanocomposite) have been characterized utilizing XRD, SEM-EDX, FTIR, UV, and TGA. This study shown that CeO-SiO2 Nanocomposite (Super Nanocomposite) outperformed SiO2 NPs and CeO NPs in terms of in vitro bioactivities. This study emphasises the importance of producing CeO-SiO2 nanocomposite (Super Nanocomposite) materials sustainably for biomedical applications.